Organizational world-class level in the continuous improvement process: case study in automotive organizations - Ferraz, Thais Cristina Pereira; de Souza, Luiz Gonzaga Mariano; Mello, Carlos Henrique Pereira (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper presents a discussion on the aspects related to the efficiency and the efficacy of the continuous improvementmanagement. The proposal of the paper is to present such practice as a technology that superpasses thelimits of the normative fulfillment of the quality management systems. For this reason, this paper based on thexx multiple case study – having as empirical elements of investigation – car enterprises from the southern regionof the state of Minas Gerais, Brazil. From the description of the investigated organizations, which characterizethe levels of organizational excellence regarding continuous improvement, it is discussed the sustentation andthe evolution of the continuous improvement concept, made feasible by the organizational learning process. Thestudy points out xx the need to articulate the training and educational activities xx as well, which are relevantin the development and maturation in the management of this technology. It xx emphasizes, therefore, the relevanceof the integration between the social and technical systems as a base for the continuous improvement, bymeans of the perfection and potentiation of the abilities which define the level of its excellence.Keywords: Continuous improvement; Quality; Maturity.